Gondolatok az erkölcsi károkhoz kapcsolódó hozzátartozói igények megengedhetőségéről - Fézer, Tamás (Debreceni Jogi Műhely, 2005)
On the very swampy field of damages for non-pecuniary loss there is a special problem called claims of relatives. These claims are also known as claims of secondary victims or third parties. In this legal situation the injury itself hurts not the claimer himself. The claimer has non-pecuniary or moral loss because of his connection with the injured person. He is not the direct and suffering subject but the one who has a loss in his personal rights.In Hungary the question is whether these claims can be permitted or not. During the changing structure of damages for non-pecuniary loss in the second half of the 20th century, this problem fitted to the actual judgement of moral damages. Now days the question is a little bit easier: in almost every decision courts admit the right of relatives to claim damages for an injury against there beloved relative, but in most of the cases they demand that plaintiffs has to demonstrate manifested losses not only the infringement of their personality rights.In this essay beside the Hungarian jurisdiction I examine German, French, English, Belgian and Dutch legal points of view too. The most interesting and – in my opinion – the one that can be useful for the upcoming new Hungarian Civil Code is the Dutch system.Dutch Civil Code limits the possibility of ‘third parties’ to claim damages for non-pecuniary loss as a result of the injury or death of another person. In typical cases the plaintiff would like to claim compensation because he suffered mental illness from witnessing the death of another person, namely a relative. This claim is not awarded by Dutch courts because of the prohibition of Civil Code, but the interpretation of the mentioned provision lives restrictively in jurisdiction. We can find two situations when the claim of third parties can be awarded. First of all, the claimant can only claim for damages, caused by a mental trauma because of being witness of an injury against another person, if he can establish that the aggressor (defendant) also committed an unlawful act vis-à-vis the claimant himself, which resulted in the trauma. It is really difficult to be demonstrated because of the causation required by BW. The process to verify that the aggressor, who committed an unlawful act against another person, causes the trauma is almost impossible in some cases. The second chance of the secondary victim to claim for compensation is if he verifies that the trauma amounts to physical or non-physical injury. If this is the case, the claimant can get compensation of his pecuniary loss (such as cost of medical treatment) and non-pecuniary loss on the basis of his non-physical personal injury.A famous case in Dutch case law is ‘Taxi bus case’. A 5-year old little girl was riding her bike close to her home, when a taxi bus overruns her. The bus actually rides over the girl’s head. The mother was immediately warned by one of the neighbours and found her daughter with her face turned to the ground. First, the mother called the ambulance hoping that the girl was still alive. When the mother tried to turn her daughter’s head to look her in the face, she experienced that her hand disappeared into the skull of the girl. The mother noticed that the substance next to her girl’s head was not, as she considered, her vomit, but appeared to be the girl’s brain itself. The mother suffered severe mental illness because of the shock of this sight and the realization. Dutch law is consequent in the question that there is no claim for non-pecuniary damages subsequent to death of a relative.  Taxi bus case was the first when Dutch Supreme Court awarded the right to compensation of non-pecuniary damages to somebody who lost his relative. The decision contained that the act committed towards the child, must also be regarded as tortuous towards the mother. The Court emphasized that there was a distinction between the consequences of the child’s death, for which no non-pecuniary damages may be awarded, and the consequences of the confrontation with the accident, for which damages may indeed be awarded. The mother received 14,000 Euros for non-pecuniary damages. This case shows that although in principle the plaintiff has a right to claim compensation for the exact damages he suffered, the courts are free to assess the damage in a more abstract way, if that corresponds better to its nature.Examining this case it is obvious that extra conditions are demanded to claim for non-pecuniary damages because of the loss of a relative. Only the fact of losing a close relative is not enough for a successful action. There have to be special circumstances, which demonstrate that the unlawful act made a direct effect to the plaintiff, who became the primary victim.The English solution is interesting because not only the relatives have right to claim but almost anybody who can verify a close relationship with the injured person. In my opinion this system ensures a more coherent and logical jurisdiction, because during the examination of authorization not only a legal fact – being a relative of the injured person – establishes the right to claim but a real emotional relationship.